Effects of habitat complexity loss on eastern slope Rocky Mountain Brook Trout populations - Herdrich, Adam T., author; Winkelman, Dana L., advisor; Walters, David M., committee member; Wohl, Ellen E., committee member (Colorado State University. Libraries, 2016)
Western U.S. rivers are currently influenced by legacy effects of reduced large wood (LW) loading and retention that has led to reduced in-stream habitat complexity. Historical land use practices such as tie-driving, snag removal, and beaver trapping have all contributed to declines in either input or retention of LW in mountain streams. Effects from these practices have persisted over a century after the activities ceased; suggesting streams have entered an alternative stable state. The alternative state is characterized by loss of multi-thread stream reaches, reduced sediment and nutrient retention, steeper channel gradient, reduced pool volume and altered pool geometry. The cumulative effects of these changes lead to narrower and shallower streams with higher width to depth ratios, and overall decreased stream and valley complexity. Using a few of the last remaining patches of old-growth forest on the Front Range of Colorado (USA), I compared population densities, individual growth rates, diet compositions, and annual prey consumption demand of Brook Trout Salvelinus fontinalis in streams across a gradient of wood volumes. Brook Trout population size was sampled via multi-pass electrofishing and approximately 30 individuals at each site were sacrificed for growth and diet studies. Individual growth was back-calculated from otolith sections, and diet composition was estimated from stomach samples collected at each site. Average growth rates and diet compositions were then combined in a bioenergetics model that provided an estimate of the amount of prey resources needed to support observed growth and population densities. Trout population density appears to be positively related to the number of pools, and standing stock biomass of aquatic insects. The scale of measurement was an important consideration in predicting trout biomass. At both the local (square-meter) and landscape (valley length) scales, standing stock biomass of aquatic insects was the best predictor of trout biomass. However, at the valley scale, the number of pools was important in predicting trout biomass in combination with of standing stock biomass of aquatic insects. Annual individual prey consumption demand did not differ between two sites with high and low wood volume and trout biomass. Therefore, total prey demand at a site was determined by population density, and less so by physical habitat. Between the two sites, however, diet compositions were significantly different during the summer season. Fish at the high wood site were consuming more small aquatic insect larvae (e.g., Family Chironomidae and Simullidae) to support growth and fish biomass, whereas diet composition at the low wood site consisted of terrestrial insects (ants) and larger aquatic insect larvae. Individual growth rates of age-1 Brook Trout were negatively affected by increasing density. However, growth for the largest and smallest individuals at each site was not affected by density. The largest fish at each site are presumably dominant individuals, and can out compete all other individuals for optimum foraging positions regardless of density, and are therefore not affected by density. While the smallest fish, presumably the most subordinate individuals, are outcompeted for resources at all densities, and are likewise not affected by increasing density. Large wood, in the correct geomorphic context, can drastically alter stream and valley habitat complexity. My results suggest the pool habitat created by LW and available prey resources can dramatically increase trout populations. However, the negative effects of historical land uses have persisted >100 years and a loss of aquatic animal production in mountain watersheds due to land use changes incurred over a century ago is occurring.